Ulama dan Perubahan Sosial: Melawan atau Berdamai dengan “Zaman Baru”? - Ulil Abshar Abdalla (Tashwirul Afkar, 2022)
The profound changes brought by modernity gave Muslims hope for a "new awakening" through modernity's promises of freedom, rationality, science and progress. However, it also had a traumatic impact on Muslims as authoritarian regimes primarily carried out modernization. This has led to religious reactions, on the one hand triggering the emergence of an Islamic revivalist movement that offers an exclusive Islamic narrative, on the other hand, triggering the reaction of ulama who try to make peace with the "new age" by reinterpreting tradition. This paper explores how the ulama responds to social change due to modernity. This paper departs from the question, is it true that ulama are always conservative and resistant to change, as is a common perception? The method of this paper is descriptive-objective, but it is not simply a detached "descriptive-objective" analysis, as if the author is not involved. The author is clearly part of and involved in the issues discussed here. An important finding of this paper is that the image of the ulama as conservative and resistant to change is a false assumption. But on the other hand, it must also be recognized that conservative elements exist in the ulama. At the same time, we also find progressivism and a desire for progress in them, although the pace of change they want is not as fast as the progressives out there expect. What appears before us is actually not a black-and-white image. There are diverse and complex dynamics in the ulama.